Digitization of the Nissen–Riesen chimpanzee radiological growth series. Issue 4 (18th June 2020) - Thompson, Nathan E.; Ahmed, Lameesah; Celebi, Taner B.; Coopee, Zachary S.; Koll, Nikki; Rubinstein, Danielle; Saunders, Megan A.; Anemone, Robert L.
Abstract: Longitudinal morphological growth data of apes are incredibly difficult to obtain. Long life histories, combined with practical and ethical issues of obtaining such long‐term data have resulted in few longitudinal data sets in chimpanzees of known chronological ages. One classic, long‐term growth study of chimpanzees was that of Drs Nissen and Riesen initiated at the Yale Laboratories of Primate Biology in 1939. Through that study, whole‐body radiological images were taken on a regular basis from a "normative" group of chimpanzees from birth to adulthood. Here we have digitized the known remaining radiographs from that growth study, many of which are deteriorating, and uploaded the data set to the free, online database MorphoSource. The database comprises 3, 568 X‐ray images of 15 of the 16 chimpanzee subjects in the normative group and 1 individual from an experimental group. Herein, we briefly review the historical context of this study and specific details of the data set.